Graphic design essentials : skills, software, and creative solutions - Macario, Joyce Walsh (Laurence King Publishing, 2009)
Creating effective, eye-catching designs and layouts is a matter of both inspiration and practical know-how. Graphic Design Essentials is the ultimate guide to great design for aspiring designers. Written by a leading teacher and practitioner, the book integrates clear explanations of the concepts behind great design with instruction in the use of the core software packages - Photoshop, Illustrator, and Indesign . It is written especially to help beginners learn the essentials of graphic design quickly and to reflect the fact that the creative process needs to involve a thorough integration of design principles with software capabilities. Illustrations and analyses of classic designs sit alongside step-by-step introductions to the design and software skills necessary to achieve powerful results. The book follows a clear formula of design concepts, examples, analysis, software skills and projects. This encourages both successful development of design fundamentals and the capability to produce graphic designs.